History of Transformational Leadership - Nurul Indana; Achmad Patoni; Binti Maunah (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2023)
Transformational leadership is a new leadership paradigm that pays more attention to the charismatic and affective elements of leadership. Therefore in this paper will describe the history of transformational leadership to understand more deeply how the emergence of transformational leadership. This research is a library research (library research) namely a series of activities related to library data collection methods. Research that uses methods to obtain information data by placing existing facilities in the library such as books, magazines, documents, records of historical stories or pure literature research related to the object of research. The analysis used using content analysis. The results of the study show that transformational leadership is leadership that is able to encourage followers to realise the importance of work results, prioritise the interests of the team/organisation, encourage achieving higher needs, maintain consistency between beliefs, verbal and actions, prohibit being inconsistent between words and deeds, be careful in calling for something, have to measure/evaluate yourself, and have to be an example before saying something. The emergence of transformational leadership relates to the development of leadership theory ranging from Trait Theory namely leadership theories that focus on the traits of leaders, then the skill theory of leadership namely leadership theory that discusses the abilities and skills of leaders in running organisations. furthermore Style Theory namely the theory related to leadership style, along with developments and needs so that transformational leadership emerges.